PLURALISME AJARAN AGAMA PADA MASA KERAJAAN BALI KUNA - Ni Gusti Ayu Agung Nerawati (Sanjiwani: Jurnal Filsafat, 2020)
During the Ancient Kingdom in Bali, religious teachings flourished well. Some sects had developed during that time before finally assimilated by MPU Kuturan. Some relics indicate the existence of these sects which can be seen in Pusering Jagat Temple and Kebo Edan Temple in Pejeng Gianyar region. At that time, the sects developed well. However, in the course of time, their leaders began to scramble to divide followers. This raises concerns that initiative to unite among them needs to be done. In order to maintain its continuity, the union is considered necessary, but by still taking the main points of each teaching. This is what causes Hinduism in Bali to look different. When it comes to plurality, Hinduism is the container, because in it the fusion of several teachings which initially contradicted, but which can be adapted slowly. This plurality becomes very important because, in essence humans are different from one another. This difference raises a different perspective. By accommodating all the elements, finally everyone feels accommodated. This is the message of pluralism in the era of Ancient Bali.